Sociolinguistic Competence in Chinese Heritage Language Speakers: Variation in Subject Personal Pronoun Expression - Zhang, Xinye (Languages (Basel), 2025)
Learning a language means both mastering the grammatical structures and using contextually appropriate language, or developing sociolinguistic competence, which has been examined by measuring the native-like patterns of sociolinguistic variables. This study investigates subject personal pronoun expression (SPE) variation in Mandarin by young adult and child heritage language learners (or Chinese Heritage Language, CHL) and explores the development of sociolinguistic competence. With data collected from 15 young adults and 27 children, regression analyses show that internal linguistic constraints, psychophysiological constraints, and social constraints all significantly affect SPE variation in CHL. Overall, CHL children used fewer subject pronouns than young adults. The use of pronouns in both child language and young adult speech is constrained by similar factors. However, the difference in SPE patterns between the two groups was not statistically significant. This suggests that children may have already established some adult-like variation patterns, but these are not further developed until early adulthood. By exploring the development of sociolinguistic competence, this research contributes to the current understanding of how sociolinguistic variables are acquired and employed in heritage language at different developmental stages.